Progression of HPV infection to detectable cervical lesions or clearance in adult women: Analysis of the control arm of the VIVIANE study. Issue 10 (15th May 2016) - Rachel Skinner, S.; Wheeler, Cosette M.; Romanowski, Barbara; Castellsagué, Xavier; Lazcano‐Ponce, Eduardo; Rowena Del Rosario‐Raymundo, M.; Vallejos, Carlos; Minkina, Galina; Pereira Da Silva, Daniel; McNeil, Shelly; Prilepskaya, Vera; Gogotadze, Irina; et al.
Abstract : The control arm of the phase III VIVIANE (Human PapillomaVIrus: Vaccine Immunogenicity ANd Efficacy; NCT00294047) study in women >25 years was studied to assess risk of progression from cervical HPV infection to detectable cervical intraepithelial neoplasia (CIN). The risk of detecting CIN associated with the same HPV type as the reference infection was analysed using Kaplan–Meier and multivariable Cox models. Infections were categorised depending upon persistence as 6‐month persistent infection (6MPI) or infection of any duration. The 4‐year interim analysis included 2, 838 women, of whom 1, 073 (37.8%) experienced 2, 615 infections of any duration and 708 (24.9%) experienced 1, 130 6MPIs. Infection with oncogenic HPV types significantly increased the risk of detecting CIN grade 2 or greater (CIN2+) versus non‐oncogenic types. For 6MPI, the highest risk was associated with HPV‐33 (hazard ratio [HR]: 31.9 [8.3–122.2, p  < 0.0001]). The next highest risk was with HPV‐16 (21.1 [6.3–70.0], p  < 0.0001). Similar findings were seen for infections of any duration. Significant risk was also observed for HPV‐18, HPV‐31, and HPV‐45. Concomitant HPV infection or CIN grade 1 or greater associated with a different oncogenic HPV type increased risk. Most women (79.3%) with an HPV infection at baseline cleared detectable infections of any duration, and 69.9% cleared a 6MPI. The risk of progression of HPV infection to CIN2+ in women >25 years in this study was similar to that in women 15–25 years in PATRICIA. Abstract : What's New? Which HPV infections lead to cancer in women over 25 years? Most cervical cancer follows persistent oncogenic HPV infection, but most HPV infections clear naturally. Thus, to best predict patient outcomes, it's imperative to understand how HPV infections progress to CINs. This study confirmed that in women over 25 years, persistent infection with HPV‐33 or HPV‐16 meant the greatest chance of developing a CIN—the same as was found in women 15–25 years, in an earlier analysis.